2012
DOI: 10.1007/s11136-012-0126-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-treatment Lyme disease syndrome symptomatology and the impact on life functioning: is there something here?

Abstract: PurposeA subset of patients treated for Lyme disease report persistent or recurrent symptoms of unknown etiology named post-treatment Lyme disease syndrome (PTLDS). This study aims to describe a cohort of participants with early, untreated Lyme disease, and characterize post-treatment symptomatology and functional impact of PTLDS over time.MethodsSixty-three participants with erythema migrans and systemic symptoms were enrolled in a prospective cohort study. Participants underwent physical exams and clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
107
2
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 38 publications
2
107
2
5
Order By: Relevance
“…These posttreatment symptoms may be mild and limited or severe and chronic. When posttreatment symptoms last 6 months or longer and impair life functioning, patients meet the case definition for posttreatment Lyme disease syndrome (PTLDS) (1,13,14). Studies have suggested a severe initial illness (15,16), delayed treatment, neurologic involvement (1,17), or suboptimal antibiotic therapy (17,18) to be potential risk factors for development of PTLDS.…”
mentioning
confidence: 99%
“…These posttreatment symptoms may be mild and limited or severe and chronic. When posttreatment symptoms last 6 months or longer and impair life functioning, patients meet the case definition for posttreatment Lyme disease syndrome (PTLDS) (1,13,14). Studies have suggested a severe initial illness (15,16), delayed treatment, neurologic involvement (1,17), or suboptimal antibiotic therapy (17,18) to be potential risk factors for development of PTLDS.…”
mentioning
confidence: 99%
“…19, 5, 2, 20 One study examined associations between clinical features that appear early in the illness and functional outcome in PTLDS patients, but did not examine the influence of prominent clinical variables that manifest after treatment. 21 Knowing the extent to which commonly reported symptoms such as cognitive impairment, pain, fatigue, or psychopathology contribute to functional impairment would enable more targeted therapies for patients with persistent symptoms, while further elucidating their specific nature and impact in PTLDS.…”
mentioning
confidence: 99%
“…Стан дитини за-довільний, знаходиться під спостереженням, оскільки після перенесеного бореліозу можуть зберігатися асте-новегетативні реакції у вигляді порушення сну, гіпер-збудливості, емоційної лабільності. Даний стан оха-рактеризовано як Post-Lyme-Disease syndromes (PLDS) і за американськими та європейськими рекомендація-ми не потребує лікування, якщо раніше була проведена адекватна антибактеріальна терапія [29].…”
Section: огляд / Reviewunclassified